DNA methylation is associated with airflow obstruction in patients living with HIV. Issue 5 (18th December 2020) - Hernandez Cordero, Ana I; Yang, Chen Xi; Obeidat, Maen; Yang, Julia; MacIsaac, Julie; McEwen, Lisa; Lin, David; Kobor, Michael; Novak, Richard; Hudson, Fleur; Klinker, Hartwig; Dharan, Nila; et al.
Abstract : Introduction: People living with HIV (PLWH) suffer from age-related comorbidities such as COPD. The processes responsible for reduced lung function in PLWH are largely unknown. We performed an epigenome-wide association study to investigate whether blood DNA methylation is associated with impaired lung function in PLWH. Methods: Using blood DNA methylation profiles from 161 PLWH, we tested the effect of methylation on FEV1, FEV1 /FVC ratio and FEV1 decline over a median of 5 years. We evaluated the global methylation of PLWH with airflow obstruction by testing the differential methylation of transposable elements Alu and LINE-1, a well-described marker of epigenetic ageing. Results: Airflow obstruction as defined by a FEV1 /FVC<0.70 was associated with 1393 differentially methylated positions (DMPs), while 4676 were associated with airflow obstruction based on the FEV1 /FVC<lower limit of normal. These DMPs were enriched for biological pathways associated with chronic viral infections. The airflow obstruction group was globally hypomethylated compared with those without airflow obstruction. 103 and 7112 DMPs were associated with FEV1 and FEV1 /FVC, respectively. No positions were associated with FEV1 decline. Conclusion: A large number of DMPs were associated with airflow obstruction and lung function in a unique cohort of PLWH. Airflow obstruction in even relatively young PLWH is associated with global hypomethylation, suggesting advanced epigenetic ageing compared with those with normal lung function. The disturbance of the epigenetic regulation of key genes not previously identified in non-HIV COPD cohorts could explain the unique risk of COPD in PLWH.